2019
DOI: 10.1186/s12985-019-1154-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological characterization of hepatitis B vaccine breakthrough infections in serial samples from two plasma donors

Abstract: Background Although vaccines for hepatitis B virus (HBV) are highly effective, HBV infections in vaccinees occur. Index samples of breakthrough infections are typically anti-HBc negative but HBV DNA positive with protective anti-HBs levels while HBsAg detection may be delayed or absent. HBsAg mutations have been associated with some vaccine breakthrough cases. Methods This research characterizes the serological and molecular profiles of vaccine breakthrough infections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Only one HSLD sample was anti-HBs-positive. Consistent with our previous observation that the HBsAgNx assay improved the detection of HBsAg in the presence of anti-HBs, 18/86 (20.9%) NAT yield and OBI samples incrementally detected by HBsAgNx were anti-HBs-positive [10,11]. However, a combination of anti-HBs >300 mIU/mL with an extremely low viral load could have limited HBsAg detection (Figure 2).…”
Section: Hbv Dna and Anti-hbs Levels Relative To Hbsagnx Detectionsupporting
confidence: 90%
See 2 more Smart Citations
“…Only one HSLD sample was anti-HBs-positive. Consistent with our previous observation that the HBsAgNx assay improved the detection of HBsAg in the presence of anti-HBs, 18/86 (20.9%) NAT yield and OBI samples incrementally detected by HBsAgNx were anti-HBs-positive [10,11]. However, a combination of anti-HBs >300 mIU/mL with an extremely low viral load could have limited HBsAg detection (Figure 2).…”
Section: Hbv Dna and Anti-hbs Levels Relative To Hbsagnx Detectionsupporting
confidence: 90%
“…None of the samples in this study had the classic sG145R mutation associated with vaccine breakthrough which has been reported at a high prevalence in some studies of OBI (Tables 2 and 3). One OBI HBsAgNx-positive-anti-HBs-positive sample had a D144N mutation, a rare mutation associated with vaccine breakthrough (Table 3) [10]. Six OBI samples had substitutions at cysteines involved in disulfide bonds within the 'a' determinant (amino acids 124-147) (Table 3).…”
Section: Sequence Analysis Of the Pres1 Pres2 And S Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamic analysis revealed that the antigenic loops in the G145R mutant are not as exposed as those in the wild-type HBsAg, with a reduced immunogenic potential that may lead to vaccine escape [15]. Until now, a few cases of HBV infection with virus harboring MHR mutations among recipients of not-plasma derived vaccines have been reported, particularly in blood donors receiving HBV DNA testing before donations [16,17]. Thus, the possible impact of HBsAg escape mutants on vaccine efficacy should be acknowledged and taken into account.…”
Section: Hbv Diagnostic Toolsmentioning
confidence: 99%
“…Hossain et colleagues recently found that two natural amino acid mutations, lysine at 120 and aspartic acid at 123, were simultaneously responsible for the production of completely undetectable HBsAg (HBsAg with complete loss of antigenicity), when tested using commercial ELISA kits (Rapid II kit from Beacle Inc., Kyoto, and HBs ELISA Kit from Bioneovan Co., Ltd., Beijing, China) [18]. Hopefully, some new HBsAg assay allows earlier detection of vaccine breakthrough infections and more sensitive detection of HBsAg in the presence of anti-HBs [17]. HBV infection should be considered in patients with acute or chronic liver damage in the absence of an alternative diagnosis and despite HBV vaccination and/or negative HBsAg testing.…”
Section: Hbv Diagnostic Toolsmentioning
confidence: 99%